Dynamics and Control of Double-Pipe Heat Exchanger - .Mousa, Khalid M (Nahrain University College of Engineering Journal, 2010)
Experimental investigation was conducted to study the dynamics of double-pipe heat exchanger using step change in flow rate of hot water and observe its effect on the temperature of cold water and it was found that the transfer function can be represented by first order system plus dead time (FOPDT).MATLAB 7.4 simulation and programming was used to show the response of close-loop system using P, PI, PID and fuzzy logic control. The Smith predictor was used to remove the effect of transport delay on the process and it was found that this method greatly improve the response of the system. The stability of the overall closed loop system was proved by using Bod plot diagram.